2001
DOI: 10.1023/a:1005676724618
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Kdc1 is a novel K+-channel gene cloned from carrot roots, and which is also present in cultured carrot cells. We investigated the characteristics of the ionic current elicited in Xenopus oocytes coinjected with KDC1 (K+-Daucus carota 1) and KAT1 (from Arabidopsis thaliana) RNA. Expressed heteromeric channels displayed inward-rectifying potassium currents whose kinetics, voltage characteristics, and inhibition by metal ions depended on KDC1:KAT1 ratios. At low KDC1:KAT1 ratios, Zn2+ inhibition of heteromeric K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This suggests the formation of heteromultimeric channels between KDC1 and DKT1 subunits. In line with the results obtained with KDC1, which forms heteromeric potassium channels with KAT1 [9], the ability of DKT1 to form heteromultimeric channels with KAT1 was also verified by the co‐expression in Xenopus oocytes. The DKT1:KAT1 channel displayed large inward rectifying currents with modified characteristics with respect to homomeric KAT1 (data not shown).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests the formation of heteromultimeric channels between KDC1 and DKT1 subunits. In line with the results obtained with KDC1, which forms heteromeric potassium channels with KAT1 [9], the ability of DKT1 to form heteromultimeric channels with KAT1 was also verified by the co‐expression in Xenopus oocytes. The DKT1:KAT1 channel displayed large inward rectifying currents with modified characteristics with respect to homomeric KAT1 (data not shown).…”
Section: Resultssupporting
confidence: 80%
“…The results presented on DKT1 localization together with the whole mount and in situ hybridisation experiments reported for KDC1, the first potassium channel isolated from carrot [7,24], demonstrate that the channels are co‐localised in many plant tissues, in roots (endodermis, epidermis and hairs), SAM and embryo cotyledons (summed up in Table 1 ), therefore suggesting a possible interaction between the two channels. It has been widely demonstrated that plant K + channels can co‐assemble [8–11,25], and we have previously shown that KDC1 can act as a modulator subunit when co‐expressed with KAT1 [9,10], we thus wanted to see if KDC1 can form functional heteromeric channels with DKT1. Interestingly, we obtained exceptionally robust and stable negative inwardly‐rectifying ionic currents in almost all oocytes which were co‐injected with KDC1 and DKT1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (25) have shown that AtKC1 seems not to form functional K ϩ channels when solely expressed in Xenopus oocytes, human embryo kidney 293 cells, or Sf9 insect cells (unpublished observations). Coexpression of AtKC1 or its orthologue KDC1 with members of other subfamilies strongly affected gating, kinetics, selectivity, and heavy metal resistance (25,30). Therefore, we studied the potassium conductance of AtKC1 expressing root hair protoplasts isolated from 7-day-old seedlings grown on filter paper.…”
Section: Atkc1 Is Predominantly Expressed In Rootsmentioning
confidence: 99%
“…Besides regulation of channel genes and proteins at the transcriptional (20) or at the posttranslational level (21), respectively, heteromeric assembly of different ␣-subunits might provide the molecular basis for the functional diversity observed in vivo (22)(23)(24). Although there is still controversy over them (25,26), biochemical and electrophysiological data suggest that, like animal potassium channels (27), different ␣-subunits of one channel family form heterooligomeric channels (18,25,(28)(29)(30).…”
mentioning
confidence: 99%